FINANCIAL PERFORMANCE OF TRUNG VUONG HOSPITAL, HO CHI MINH CITY IN THE PERIOD OF 2022-2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the financial performance of Trung Vuong Hospital in Ho Chi Minh city during the period 2022-2024.Methods: A cross-sectional descriptive study was conducted using a structured checklist to retrospectively collect secondary data from the hospital’s financial statements, annual activity reports, and human resource reports for the years 2022-2024. Data were aggregated and descriptively analyzed by year and by groups of financial indicators.Results: Total hospital revenue increased from 419.6 billion VND in 2022 to 556.2 billion VND in 2023 and 649.2 billion VND in 2024. Revenue from medical examination and treatment services accounted for approximately 86-90% of total revenue, with health insurance-reimbursed services representing the main revenue source at over 70%. Recurrent expenditure rose from 419.6 billion VND to 525.6 billion VND and 621.6 billion VND, primarily driven by professional activities (70-73%) and personnel-related costs (27-30%). The balance between revenue and expenditure was nearly neutral in 2022, and shifted to a surplus of around 30 billion VND in 2023 and 27 billion VND in 2024. This surplus was mainly allocated to salary reform and additional staff income, while allocations to the career development fund remained limited.Conclusion: The financial performance of Trung Vuong Hospital in 2022-2024 demonstrates a trend of recovery and growth in both revenue and expenditure, with a positive revenue-expenditure balance. However, the level of accumulation for long-term investment and service development remains modest.
Keywords: Financial performance, revenue-expenditure balance, Trung Vuong Hospital, financial autonomy